INTELLIGENCE DIAGNOSTIC METHODS IN MODERN CONDITIONS - SHELESTOVA, O. (Herald of Kyiv Institute of Business and Technology, 2024)
Research on the level of intelligence, its abilities, and disorders in clinical psychology and psychiatry encompasses clinical, psychological, and psychopathological assessment. IQ tests are used to determine the overall intellectual development of individuals. A group of general cognitive ability tests, including various methodologies such as CAT, CF, Wechsler, TUS, Anthauer, Raven, and analogies, are employed to evaluate the level of intellectual abilities. The article presents various approaches to understanding intelligence and methods of analysis. TUS, Anthauer test, mixed tests make it possible to determine innate and acquired intelligence, the assessment of which is possible indirectly with regard to the peculiarities of thinking, in particular, understanding the figurative meaning of proverbs and sayings, general awareness, which primarily form the basis of the Wechsler test. Experimental psychological testing can clarify the nature and severity of intellectual decline. John Raven’s progressive matrices test is used for this, consisting of 30 and 60 tasks divided into 5 series. Each series presents an image of a canvas with a geometric pattern or several matrices with one part missing. The research participant is asked to identify patterns in the matrices and choose the one that is missing from the six or eight offered in the complete picture. The results are evaluated by the number of correctly selected missing fragments for each task. The CAT belongs to the category of tests of mental abilities (IQ), acting as an adaptation of the Vanderlik test. Its structure corresponds to the structure of general possibilities. As a result of the adaptation, almost half of the texts of the tasks were changed, and the structure of the test was adjusted to the structure of general abilities. The basis of the test is P. Vernon’s hierarchical model of learning ability, which consists in the fact that the factors that determine abilities can be divided into several levels, where factors of a lower level are derivatives of factors of a higher level.